Simple Cash Flow Training and Halal Product Process Assistance to the Fishery Processing Group of Sungsang 1 Village Banyuasin II Sub-District - Mail Hilian Batin; M. Junestrada Diem; Rika Lidyah; Rini Ariyanti; Supriana (Jurnal Aksi Dosen dan Mahasiswa, 2023)
Along with the development of the business world, it requires business actors to be able to continue to grow so as to generate optimal profits and be able to maintain their business success, but many of them pay less attention to the quality standards of the products produced. This makes the products produced less suitable for consumption both by health standards and religious law (halal). This situation changes the level of consumer awareness to be more critical of what they will consume. The concept of halal products is now starting to be widely discussed and is considered to be a standard for a product. The purpose of including a halal label with a halal certificate is to increase market share and sales numbers. Next, meet the demands and give satisfaction to consumers. Improve product quality, fulfill interest and comfort to consumers, especially Muslim consumers. Providing halal and safe food is a very prospective business, because through halal certification and labeling can invite loyal customers who are not only in demand by Muslims but also non-Muslim communities. Halal food for Muslims is proven to be of high quality and very good for the health of the human body. The existence of halal certification-labeling not only aims to provide inner peace to Muslims but also peace of production for business actors.